Strengthening Edukreatif Branding in Dadap Village Community, South Tangerang Through Digital Communication - Iman, Fauzi Nur; Mansur, Suraya; Saragih, Nurhayani; Wahyudi, Sophan; Octory, Gadis (Jurnal Abdi Masyarakat (JAM), 2025)
The South Tangerang City Government, Banten, welcomed the selection of West Dadap Village as an Independent, Food Secure, Clean, and Superior Village (Mantul) because it supports the Village Development program criteria. Therefore, Dadap Village was formed into an independent village and an educational tourism destination for the community in 2022. This community service activity fulfils the University's Additional Performance indicators, namely strengthening the competence of Partners in the fields of craft production, Packaging Management, Branding, and digital marketing to strengthen the Edukreatif Branding of Dadap Village. The solution offered is to transfer knowledge through training in making souvenirs unique to Dadap Village in the form of Chunky Bags, Product Packaging, Branding, Product Photography as marketing content and digital marketing. The target output is to produce competency strengthening in the fields of creativity in crafting souvenirs, packaging, branding, product photos and digital marketing. Second, produce outputs in the form of Chunky bag souvenirs, posters, activity videos, publications on online news portals, scientific journal articles accredited by Sinta and HAKI copyrights.